Designing Software Define Network Prototypes with Open vSwitch as Monitoring Traffic Police on The Raspberry Pi - Aldy Mohamad; Purnawarman Musa (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2020)
Technology is growing from year to year even day to day, this has made the increasing need for infrastructure that supports especially in aspects of computer networks. The increasing number of traffic that is burdening the router or switch encourages the increasing number of nodes to network devices with the aim of reducing and dividing the burden on network traffic. The need for traffic management and control is very important because with the increasing number of network devices and the higher traffic, making a network administrator need more time to handle if there are problems in the network. This research is trying to implement open vSwitch technology on low-cost raspberry pi devices. And by applying the traffic shaping and traffic rate methods by utilizing the traffic control feature on Linux, and then try to divide the amount of traffic received by network devices so that the traffic load becomes controlled. The results of this study, show the results of successful implementation and traffic management work well.